КУШОНЛАР ҲУКМРОНЛИГИ ДАВРИДА ШИМОЛИЙ БАКТРИЯДАГИ ДИНИЙ ЭЪТИҚОДЛАР - Назаров Х. А.; Одилова Н. З. (TARIXIY TADQIQOTLAR, 2025)
This study examines the religious traditions and cults that existed in Northern Bactria during the rule of the Kushan Kingdom, as well as their influence on the cultural and political development of the region. Particular attention is given to the pantheon of supreme deities of the Kushan state, the study of which is complicated by the complex religious landscape of the era, characterized by the coexistence and mutual influence of Zoroastrianism, Buddhism, Hinduism, Hellenistic cults, and indigenous beliefs.